Mechanical strength improvement of aluminum foam-reinforced matrix for molten carbonate fuel cells - Lee, Mihui; Lee, Chang-Whan; Ham, Hyung-Chul; Han, Jonghee; Yoon, Sung Pil; Lee, Ki Bong (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
During the cell operation of molten carbonate fuel cells (MCFCs), matrix cracks caused by poor mechanical strength accelerate cell performance degradation. Therefore, for a stable long-term cell operation, the improvement of mechanical properties of matrix is highly required. In this study, aluminum foam was used to enhance the mechanical strength of the matrix as a 3D (three dimensional) support structure. Unlikely conventional matrix (pure alpha-LiAlO2 matrix) which has paste-like structure at the MCFC operating temperature, Al foam-reinforced alpha-LiAlO2 matrix has significantly strong mechanical strength because the 3D network structure of Al foam can form the harden alumina skin layer during a cell operation. As a result, the mechanical strength of the Al foam-reinforced alpha-LiAlO2 matrix was enhanced by 9 times higher than the pure alpha-LiAlO2 matrix in a 3-point bending test. In addition, thermal cycle test showed notable cell stability due to strong mechanical strength of Al foam-reinforced alpha-LiAlO2 matrix. The Al foam-reinforced alpha-LiAlO2 matrix shows appropriate microstructure to preserve the liquid electrolyte when performing the mercury porosimeter analysis and differential pressure test between anode and cathode. Moreover, evaluation of stability and durability for a long-term cell operation were demonstrated by single cell test for 1,000 h. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: LONG-TERM OPERATION; ALPHA-LIALO2 MATRICES; FABRICATION; STABILITY; LIALO2